Comparative genomic of methicillinresistant staphylococcus aureus PR01 (MRSAPR01) and methicillin-sensitive staphylococcus aureus SA D22901 (MSSA SAD22901) and methicillin resistant derivatives of the latter - Shien, Lee Lian (2014)
Staphylococcus aureus is a major contributor of nosocomial infections of humans in the world. This study elucidates the genomic sequences of an MRSA (MRSA PR01) isolate from a patient with septicaemia in Kuala Lumpur, a clinical methicillinsusceptible S. aureus (MSSA) isolate (SA D22901), and two in vitro generated strains CR and COR which are derivatives of SA D22901 that developed resistance to antibiotics. CR and COR were isolated by exposing SA D22901 to become resistant to the antibiotics ciprofloxacin, and ciprofloxacin and oxacillin, respectively. These S. aureus strains were sequenced using a second generation sequencing platform. A combination of de novo and comparative assemblies, annotation and genome finishing was then applied to sequenced data to obtain the finished or draft genomes. The MRSA PR01 genome was sequenced to “noncontiguous- finished” status, whereas MSSA SA D22901 was sequenced to “improved high-quality draft” status and the derivatives CR and COR were assembled using reference mapping to MSSA D22901. MRSA PR01 has an extended antibiotic resistance pattern, and is resistant to many classes of antibiotics. Multi locus sequence typing analysis determined it to be of type ST239, a prevalent healthcare lineage across the world. SA D22901 contains a novel MLST profile, and is phylogenetically diverse from other S. aureus strains found in Malaysia. Genomic analysis of MRSA PR01 provides evidence of its adaptation to survive in a health care setting through acquisition of drug and antiseptic resistance genes encoded on mobile genetic elements, large chromosomal insertions and point mutations in housekeeping genes. Comparative analysis of the clinical MRSA and MSSA strains showed the importance of genes involved in cell wall synthesis in the acquisition of methicillin resistance. Variant analysis of the in vitro generated strains has uncovered mutations and mechanisms important in the evolution of ciprofloxacin and oxacillin resistance in S. aureus. Ciprofloxacin resistance was attained via mutations in two topoisomerase genes, while mutations in genes involved in cell wall synthesis and cell adhesion were found in the oxacillin-resistant COR strain. In conclusion, this study provided the whole genome sequences of several clinical and laboratory generated S. aureus strains and identified several key features that are involved in conferring antibiotic resistance.